Decolorization of textile dyeing wastewater by Phanerochaete chrysosporium - Cing, S; Asma, D; Apohan, E; Yeşilada, O (Folia microbiologica, 2003)
The potential use of fungal pellets for decolorization of the textile dyeing wastewater was evaluated. The live pellets of the fungus Phanerochaete chrysosporium were found to remove more than 95% of the color of this wastewater within 1 d. The dye-removal capacity was a function of time and was proportional to the agitation rate; the optimum temperature was 30 degrees C. Both live and dead pellets were further examined in a repeated-batch mode for 5 d. The decolorization performance of live pellets remained high and stable for 5 d and they showed twice to thrice higher decolorization capacity than dead pellets.
Keywords: Biodegradation, Environmental; biodegradace; indoly; Water Pollutants, Chemical; Indoles; Textile Industry; chemické látky znečišťující vodu; Phanerochaete; textilní průmysl